Association between Oral Health Indicators in 13- to 15-years-old Children of ELSPAC Group Brno and Parental Educational Level - M. Kukletová; L. Izakovičová Hollá; Z. Broukal; K. Musilová; L. Kukla (Czech Dental Chamber, 2013)
Introduction: A considerable body of evidence has shown that the parental educational level (PEL) as well as health status in early childhood play a significant role in child dental caries. A multicentric European Longitudinal Study of Pregnancy and Childhood (ELSPAC) conducted also in Brno collected a great amount of data from clinical and socio-economic areas related to children's general health. Aim: To assess the relationship between caries experience and gingivitis manifestation in 13-years-olds to 15-years-olds and the PEL of their parents in a retrospective case-series study. Methods: Randomly selected children from an ELSPAC cohort in Brno (n = 780) were orally examined and their dental status (D3MFT [WHO criteria]) and gingivitis were recorded. Data on the PEL were retrieved from the ELSPAC database. Correlations between both DMFT and GI vs PEL were calculated using ANOVA and χ2-test. (Statistica v. 8.0., Statsoft Inc., Tulsa, USA.) Results: Mothers' (but not fathers') educational level significantly negatively correlated with D3MFT scores of children (p < 0.05). Similar correlation between GI and PEL was not found. Conclusion: The study confirmed a significant correlation of the educational level of mothers and caries experience in children (p < 0.05), while the correlation between GI and PEL was not significant.